Bilingualism and processing speed in typically developing children and children with developmental language disorder. - Park J.S.; Miller C.A.; Sanjeevan; T.; van Hell J.G.; Weiss D.J.; Mainela-Arnold E. (American Speech-Language-Hearing Association, 2022)
Purpose:
The aim of the current study was to investigate whether dual language experience modulates processing speed in typically developing (TD) children and in children with developmental language disorder (DLD). We also examined whether processing speed predicted vocabulary and sentence-level abilities in receptive and expressive modalities.
Method:
We examined processing speed in monolingual and bilingual school-age children (ages 8–12 years) with and without DLD. TD children (35 monolinguals, 24 bilinguals) and children with DLD (17 monolinguals, 10 bilinguals) completed a visual choice reaction time task. The Clinical Evaluation of Language Fundamentals, the Peabody Picture Vocabulary Test, and the Expressive Vocabulary Test were used as language measures.
Results:
The children with DLD exhibited slower response times relative to TD children. Response time was not modified by bilingual experience, neither in children with typical development nor children with DLD. Also, we found that faster processing speed was related to higher language abilities, but this relationship was not significant when socioeconomic status was controlled for. The magnitude of the association did not differ between the monolingual and bilingual groups across the language measures.
Conclusions:
Slower processing speed is related to lower language abilities in children. Processing speed is minimally influenced by dual language experience, at least within this age range.